Vertical price transmission analysis: the case of milk in the Slovak dairy sector - Lajdová , Zuzana; Bielik , Peter (Applied Studies in Agribusiness and Commerce, 2013)
Testing for nature price transmission and calculating elasticities of price transmission are important areas of research for providing insights into market efficiency issues. Symmetric or asymmetric price transmission has been the subject of considerable attention in agricultural economics. The concept of the price transmission is an important area of the research particularly in relation to the assessment of impact on the welfare of the vertical entities. The main goal of the paper is an analysis of the price transmission and its exploitation in case of price elasticity estimation in dairy sector. Work investigates vertical price transmission of milk in the Slovak agri-food chain. The research is based on Vector Error Correction Model (VECM) of the selected commodities at producer, processor and consumer level and the estimation of the parameters specified in the model. Moreover the paper determines the coefficient of elasticity of price transmission (EPT).